Gender difference in the association of coping styles and social support with psychological distress among patients with end-stage renal disease - Wang,Qi; Liu,Hongjian; Ren,Zheng; Xiong,Wenjing; He,Minfu; Fan,Xinwen; Guo,Xia; Li,Xiangrong; Shi,Hong; Zha,Shuang; Qiao,Shuyin; Zhao,Hanfang; et al. (PeerJ, 2020)
Objectives The study aimed to explore the association of coping styles and social support with psychological distress among patients with end-stage renal disease (ESRD) as well as gender differences in these associations. Methods A cross-sectional study of 769 ESRD patients was conducted at 25 hospitals in Qiqihar City, China. All information was collected using structured questionnaires that were self-administered by the patients. Patients’ psychological health status, coping styles and perceived social support were measured using the 12-item General Health Questionnaire, the Medical Coping Modes Questionnaire and the Multidimensional Scale of Perceived Social Support. Student’s t test, analysis of variance (ANOVA) and binary logistic regression analysis were used for data analysis. Results A total of 72.3% of participants reported psychological distress, and the prevalence of distress was higher in females (77.0%) than in males (68.8%). The usage of the acceptance-resignation coping style was positively related to psychological distress (B = 0.459, P < 0.001). Social support level was negatively associated with psychological distress (B = −0.049, P < 0.001). The use of the confrontation style was negatively related to psychological distress in females (OR = 0.87, 95% CI [0.78–0.96]) but not in males (OR = 0.98, 95% CI [0.91–1.06]) (P for interaction term = 0.007). Conclusions Greater use of the acceptance-resignation style and lower social support are related to a higher risk of psychological distress. Greater use of the confrontation style is related to a lower risk of psychological distress in females but not in males.
Keywords: Coping styles; End-stage renal disease; Psychological distress; Social support